Stacked topological insulator built from bismuth-based graphene sheet analogues - Rasche, Bertold; Isaeva, Anna; Ruck, Michael; Borisenko, Sergey; Zabolotnyy, Volodymyr; Buechner, Bernd; Koepernik, Klaus; Ortix, Carmine; Richter, Manuel; Van Den Brink, Jeroen (Nature Materials, 2013)
Commonly, materials are classified as either electrical conductors or insulators. The theoretical discovery of topological insulators has fundamentally challenged this dichotomy. In a topological insulator, the spin-orbit interaction generates a non-trivial topology of the electronic band structure dictating that its bulk is perfectly insulating, whereas its surface is fully conducting. The first topological insulator candidate material put forward - graphene - is of limited practical use because its weak spin-orbit interactions produce a bandgap of ∼ 0.01 K. Recent reexaminations of Bi 2Se3 and Bi2Te3, however, have firmly categorized these materials as strong three-dimensional topological insulators. We have synthesized the first bulk material belonging to an entirely different, weak, topological class, built from stacks of two-dimensional topological insulators: Bi14Rh3I9. Its Bi-Rh sheets are graphene analogues, but with a honeycomb net composed of RhBi 8 cubes rather than carbon atoms. The strong bismuth-related spin-orbit interaction renders each graphene-like layer a topological insulator with a 2,400 K bandgap. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20